OP0016 Tribbles homolog 3 mediates the stimulatory effects of tgf-beta on fibroblast activation and dermal fibrosis in systemic sclerosis. (23rd January 2014) - Tomcik, M.; Palumbo-Zerr, K.; Avouac, J.; Horn, A.; Khodzighorova, A.; Zerr, P.; Dees, C.; Distler, A.; Beyer, C.; Becvar, R.; Senolt, L.; Distler, O.; et al.
Abstract : Background: Tribbles Homolog 3 (TRB3), is a member of the family of pseudokinases called Tribbles which regulate activation of various intracellular signaling pathways with roles extending from mitosis and cell activation to apoptosis and modulation of gene expression. Objectives: To investigate the role of TRB3 in the pathologic activation of fibroblasts in systemic sclerosis (SSc). Methods: Activation of TRB3 was determined by real-time PCR, immunohistochemistry and immunofluorescence. Collagen synthesis was quantified by real-time PCR and SirCol collagen assay. A plasmid construct overexpressing TRB3 was designed. TRB3 expression was inhibited in cultured fibroblasts and murine models of fibrosis via siRNA. The mouse models of dermal fibrosis induced by bleomycin and attenuated adenovirus overexpressing a constitutively active TGF-β receptor I were used. Results: Increased expression of TRB3 was detected in the upper layer of the dermis of SSc patients and colocalized with prolyl-4-hydroxylase, αSMA and phosphorylated Smad3 expression. The overexpression of TRB3 persisted in cultured SSc fibroblasts (4.1±0.4-fold increase, p<0.001). Stimulation of cultured fibroblasts with TGF-β increased TRB3 protein expression by 4.5±0.2-fold (p<0.001), interestingly, these stimulatory effects were abrogated upon transfection with Smad3 siRNA. Overproduction of TRB3 in fibroblasts transfected with a plasmid construct overexpressing TRB3 increased collagen production and expression of pSmad3, lucipherase activity of col1a2 promoter reporter and Smad3 (CAGA) adenovirus reporter. Knockdown of TRB3 by siRNA abrogated the stimulatory effects of TGF-β on the release of collagen, induction of pSmad3 expression and formation of stress fibers. Moreover, mice lacking TRB3 were protected from experimental fibrosis. In the model of bleomycin-induced fibrosis, siRNA mediated knockdown of TRB3 decreased dermal thickening by 50±1% (p<0.05), hydroxyproline content by 76±5% (p<0.01) and myofibroblast counts by 86±10% (p<0.05). In mice infected with adenovirus overexpressing constitutively active TGF-β receptor I, knockdown of TRB3 decreased dermal thickening by 91±6% (p<0.05), completely prevented the accumulation of hydroxyproline (p<0.01) and decreased the myofibroblast counts by 82±7% (p<0.05). Consistent with the crucial role of TRB3 for TGF-β signaling in vitro, knockdown of TRB3 abrogated the nuclear accumulation of pSmad3 and prevented the induction of TGF-β target genes such as Smad7 and CTGF in both mouse models. Conclusions: This is the first study on the key role of TRB3 in fibroblast activation and tissue fibrosis in SSc. TRB3 is upregulated in SSc and in experimental fibrosis in a TGF-β dependent manner. TRB3 is essential for the pro-fibrotic effects of TGF-β and inhibition of TRB3 completely prevents the stimulatory effect of TGF-β. In addition, knockdown of TRB3 protected from experimental dermal fibrosis in different mouse models. Considering the potent anti-fibrotic effects in this study, TRB3 might be a promising candidate for molecular targeted therapies of SSc. Acknowledgements: This study was performed with support of CMH Research Projects No 00000023728. Disclosure of Interest: None Declared